2021
DOI: 10.3390/ijms22126515
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Processed Aloe vera Gel in Intestinal Tight Junction: An In Vivo and In Vitro Study

Abstract: Leaky gut is a condition of increased paracellular permeability of the intestine due to compromised tight junction barriers. In recent years, this affliction has drawn the attention of scientists from different fields, as a myriad of studies prosecuted it to be the silent culprit of various immune diseases. Due to various controversies surrounding its culpability in the clinic, approaches to leaky gut are restricted in maintaining a healthy lifestyle, avoiding irritating factors, and practicing alternative med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…21) Furthermore, Phan et al showed that aloe vera gel treatment induced ZO-1 expression by accelerating 4E-BP1 phosphorylation at the threonine 70 position in Caco-2 cells. 22) These results suggest that the regulation of ZO-1 expression in Caco-2 cells may be related to the activation of PI3K/Akt/ mTOR signaling and phosphorylation of 4E-BP1.…”
Section: Identification Of Gene Expression Changes Following Hme Trea...mentioning
confidence: 66%
“…21) Furthermore, Phan et al showed that aloe vera gel treatment induced ZO-1 expression by accelerating 4E-BP1 phosphorylation at the threonine 70 position in Caco-2 cells. 22) These results suggest that the regulation of ZO-1 expression in Caco-2 cells may be related to the activation of PI3K/Akt/ mTOR signaling and phosphorylation of 4E-BP1.…”
Section: Identification Of Gene Expression Changes Following Hme Trea...mentioning
confidence: 66%
“…It can be a functional food in the activation of lipolysis and the prevention of metabolic changes related to obesity since the phytosterols of Aloe gel are effective in reducing visceral fat due to the interaction with cholesterol and also has an effect on glucose metabolism, reducing blood sugar in the experimental mouse model [100]. It acts in intestinal disorders (combats constipation) due to its laxative, anti-dysenteric, anti-hemorrhoidal, and cicatrizing properties [101][102][103]. Moreover, even AV flowers are consumed more often today, knowing that diets rich in antioxidants reduce the risks of cardiovascular diseases and cancers [104].…”
Section: Biological and Pharmacological Effects Of Aloe Veramentioning
confidence: 99%